Hans Christian Andersen between a culture of meaning and a culture of presence - Davidsen, Mogens (Aktualitet - Litteratur, kultur og medier, 2019)
The article opens with questioning what kind of “community” Hans Christian Andersen as an artist can be said to have been a part of, considering that the community of Andersen’s upbringing was radically different from the one he was socialized into through his literary career. With the point of departure in Hans Ulrich Gumbrecht’s distinction between literature displaying “presence in language” and “presence achieved against language”, the article suggests that part of Andersen’s work (with Søren Kierkegaard’s critique of the novel Only a Fiddler in focus) can be seen as examples of presence achieved against language. With the two presence categories which Gumbrecht typologically distinguishes as a “presence culture” and a “meaning culture” in mind, the presence categories are ascribed to an oral culture of Andersen’s social background, and the elitist intellectual culture of the Danish Golden Age. Inspired by Kierkegaard’s characterization of Andersen’s novel in musical terms, the article further presents a possible understanding of presence, the implications of which reaches far beyond the harmonic paradigm of the Golden Age and into the musical modernism of Arnold Schönberg in the twentieth century.